Assessment of wind and solar PV local complementarity for the hybridization of the wind power plants installed in Portugal - Couto, António (2021)
ABSTRACT: To decarbonize electrical power systems, it is essential to incorporate a high share of variable renewable energy sources while minimizing their costs. An important step towards this goal includes exploring the potential for the so-called hybrid renewable power plants through the combination of (existing) wind and solar power parks. Although that is not the usual approach in their design, hybrid power plants should take advantage of existing synergies, as generation complementarity among the renewable generation technologies, and benefit from using existing infrastructures and the same grid connection point. This investigation assesses the potential of existing Portuguese wind parks for hybridization with solar power photovoltaic generation. Correlation and energy metrics for assessing the complementarity at hourly and daily periods are applied to quantify existing synergies. Results show a high potential for hybrid power plants: levels of complementarity between wind and solar resources are globally high thus allowing to increase the share of variable renewable energy sources with minimal energy curtailment, when compared with scenarios of overplanting additional wind power capacity. The highest and most consistent levels of complementarity are found in the interior regions of central and northern Portugal. The research shows that Portugal has privileged weather conditions that allow the concept of hybrid power plants to be largely explored and extended on a large and efficient scale. This outcome, which may be replicated for other countries, is an important contribution to increasing the penetration of renewable energy in electrical power systems while minimizing the overall costs of renewable energy.